Social Support Networks During the COVID-19 Pandemic - Lara Corro, Erik Said; Mina, María Roberta; Vega, Yamila (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2024)
The SARS-CoV-2 virus pandemic has caused several social and economic problems. The context of crisis and uncertainty shows us how people –as individuals and as social groups– mobilize in the name of "solidarity". This ethnographic account analyzes the construction and articulation of social support networks from different social spaces of the Partido de San Andrés de Giles. Attention is focused on processual and relational dimension of networks – based on community, kinship and reciprocity. These characteristics produced a field of actions, strategies and organizations to face the socio-sanitary crisis. We consider that this must receive special attention from social anthropology.